The Imagination of Interconnection: Laudato Si’ and Celtic Christian Spirituality - Vaughan, Kevin (The Trumpeter)

(untitled) (Athabasca University Press, 2018)
This article brings Pope Francis’s encyclical on the environment, Laudato Si’: On Care for Our Common Home, into conversation with the modern spiritual movement of Celtic Christian spirituality, arguing that its contribution to Francis’ concept of an “integral ecology lived out joyfully and authentically” is its placing the imagination at the heart of interconnectivity. The paper will begin with a description of Francis’ concept of integral ecology, outlining its biblical foundations and spiritual import. Then it will introduce the recent movement in ‘Celtic’ Christian spirituality, arguing how, despite strong criticisms from Celtic scholars, it remains an important and influential spiritual movement that speaks to the concerns, aspirations, and insights of many people within contemporary Christian culture. One of those insights is in the role of the imagination in understanding humanity’s relation to its environment, which will be explored through the movement’s engagement with Alexander Carmichael’s Carmina Gadelica. And finally, the article will conclude with how the emphasis on the imagination links to contemporary understandings of the religious imagination and how its liberating and concretizing function can serve as a psychological and theological precondition for the incarnational principle of social justice as found in Oscar Romero’s address, “The Political Dimension of the Faith from the Perspective of the Option for the Poor.”